Development of an interprofessional competency framework for collaborative practice in Japan. Issue 4 (4th July 2018) - Haruta, Junji; Yoshida, Kazue; Goto, Michiko; Yoshimoto, Hisashi; Ichikawa, Shuhei; Mori, Youhei; Yoshimi, Kenji; Otsuka, Mariko
ABSTRACT: Rapid aging of the population necessitates improved collaboration among healthcare professionals. Unfortunately, interprofessional collaboration has yet to be implemented effectively in Japan. Therefore, we aimed to develop an interprofessional competency framework for Japanese healthcare professionals. The project was conducted as a four-step process, starting with initial categorization of potential competency domains, , followed by guiding principle and prototype development, feedback on the prototype, and final consensus. First, authors (JH and MO) collected opinions about competency in interprofessional collaboration at two academic meetings of the Japan Association for Interprofessional Education (JAIPE) and then analyzed the data thematically. Second, a project team consisting of JAIPE and University representatives extracted the domains and statements as prototype 1. Third, seven representatives from professional organizations joined the project team and developed prototype 2. We then called for feedback on the revised prototype 2 at both an open symposium and via public comments. Following revision of prototype 2, a new project team including 20 university, professional organization and health practitioner representatives finally discussed prototype 3, developed the final draft and reached a consensus. In analysis after collecting the data, we extracted 11 themes. We developed four key principles which applied to six domains as prototype 1–3. Finally, our competency framework included two core domains of "Patient-/client-/family-/community-centered" and "Interprofessional communication", and four peripheral domains of "Role contribution", "Facilitation of relationships", "Reflection" and "Understanding of others". We developed an interprofessional competency framework in Japan which consists of two core and four peripheral domains. The interprofessional competency framework is likely to affect the understanding of "high-context" and "relationalism" in Japanese healthcare. We hope that our interprofessional competency framework will encourage the systematic implementation of interprofessional education and collaboration in Japan.